Short hairpin ribonucleic acid constructs targeting insulin‐like growth factor binding protein‐3 rehabilitated dyslipidaemia in diabetic rats. (16th April 2015) - Zhou, Z.‐Y.; Cheng, S.‐P.; Huang, H.; Wang, J.; Pan, H.; Liu, C.‐M.; Xing, C.; Sun, Y.‐L.; Liu, R.‐H.; Zhong, G.‐J.
Summary: It was investigated whether short hairpin ribonucleic acid constructs targeting insulin‐like growth factor binding protein‐3 (IGFBP‐3 shRNA) can rehabilitate dyslipidaemia in streptozotocin‐induced diabetic rats. After 12 weeks of intracavernous administration of IGFBP‐3 shRNA, intracavernous pressure responses to electrical stimulation of cavernous nerves were evaluated. The concentrations of serum low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol, triglyceride and cavernous cyclic guanosine monophosphate were all detected by enzyme‐linked immunosorbent assay. The per cent of smooth muscle in corpus cavernous tissue was also evaluated. It was found that the cavernosal pressure was significantly increased in the IGFBP‐3 shRNA treatment group compared to the diabetic control group after 12 weeks of intracavernous administration of IGFBP‐3 shRNA ( P < 0.01). The concentrations of serum low‐density lipoprotein cholesterol and triglyceride were significantly decreased in the IGFBP‐3 shRNA treatment group compared to the diabetic control group, while no significant changes of serum high‐density lipoprotein cholesterol concentration were found ( P < 0.01). At the same time, cavernous cyclic guanosine monophosphate concentrations and the percentage of cavernosal smooth muscle were both significantly increased in the IGFBP‐3 shRNA treatment group compared to the diabetic control group ( P < 0.01). This study indicated that IGFBP‐3 shRNA might rehabilitate erectile function via a decrease in concentrations of serum low‐density lipoprotein and triglyceride, an increase in the percentage of cavernosal smooth muscle and an improvement in the nitric oxide‐cyclic guanosine monophosphate signalling activities in streptozotocin‐induced diabetic rats.